Inflammasome‐induced extracellular vesicles harbour distinct RNA signatures and alter bystander macrophage responses - Christina F. Budden; Linden J. Gearing; Romina Kaiser; Lena Standke; Paul J. Hertzog; Eicke Latz (Journal of Extracellular Vesicles, 2021)
Abstract Infectious organisms and damage of cells can activate inflammasomes, which mediate tissue inflammation and adaptive immunity. These mechanisms evolved to curb the spread of microbes and to induce repair of the damaged tissue. Chronic activation of inflammasomes, however, contributes to non‐resolving inflammatory responses that lead to immuno‐pathologies. Inflammasome‐activated cells undergo an inflammatory cell death associated with the release of potent pro‐inflammatory cytokines and poorly characterized extracellular vesicles (EVs). Since inflammasome‐induced EVs could signal inflammasome pathway activation in patients with chronic inflammation and modulate bystander cell activation, we performed a systems analysis of the ribonucleic acid (RNA) content and function of two EV classes. We show that EVs released from inflammasome‐activated macrophages carry a specific RNA signature and contain interferon β (IFNβ). EV‐associated IFNβ induces an interferon signature in bystander cells and results in dampening of NLRP3 inflammasome responses. EVs could, therefore, serve as biomarkers for inflammasome activation and act to prevent systemic hyper‐inflammatory states by restricting NLRP3 activation in bystander cells.